(untitled) (Damascus University Journal of agriculture sciences, 2021)
The research was conducted at the Biological Control Studies and Research Center, Faculty of Agriculture Engineering, Damascus University, during the 2017 season. The aim of this study was to study the effect of four fixed temperatures (15, 20, 25 and 30 °Celsius) on the feeding and growth of the larvae of Mottled water hyacinth weevil, Neochetina eichhorniae (Coleoptera : Curculionidae on Water hyacinth (Eichhornia crassipes) to contribute to the future management of water hyacinth. The results showed that the effect of temperature on the effectiveness of N. eichhorniae larvae in feeding on the water hyacinth plant showed an increase in the rate of damage at high temperature. The lowest value of wet weight / Larva / day) (0.01) g at a temperature of 15 °c, and the results did not differ for the length of the petiole. The results showed that the highest damage to the petiole due to the feeding of N. eichhorniae larvae was at 30 °C, and the lowest was at 15 °C. High temperature was the most suitable for larval growth than at the low temperatures. The larvae presented at 30 ° C (third instar) where with the highest width of head capsule (0.69 mm), while larvae presented at temperature of 15 ° C (first instar) were with the lowest width of head capsule (0.26 mm). The study proved the effect of temperature on dry and wet weight of the beetle larvae. The average wet weight of larvae at 17 days age, was 1.1, 1.7, 2.2 and 4.8 mg at temperature degree 15, 20, 25 and 30 °c respectively. For dry weight, the results were similar, the average dry weight of larvae a 17-day age was 0.10, 0.15, 0.25 and 0.55 mg at 15, 20, 25 and 30 °c, respectively.